Efficient industrial dye decolorization by Bacillus sp. VUS with its enzyme system - Dawkar, Vishal V.; Jadhav, Umesh U.; Tamboli, Dhawal P.; Govindwar, Sanjay P. (Ecotoxicology and Environmental Safety, 2010)
This work presents role of different enzymes in decolorization of industrial dye Orange T4LL by Bacillus sp. VUS. Bacillus sp. strain VUS decolorized dye Orange T4LL, under static anoxic condition in 24 h. During decolorization of Orange T4LL a significant induction in the activities of lignin peroxidase, tyrosinase, and reductases (NADH-DCIP, azo, and riboflavin) was observed. The biodegradation was monitored by Ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, and high performance liquid chromatography. The final products 4-methyl-2-o-tolylazo-benzene-1,3-diamine and [3-(phenyl-hydrazono)-cyclohexa-1,4-dienyl]-methanol were characterized by gas chromatography-mass spectroscopy. Phytotoxicity, COD, and BUD revealed non-toxicity of degraded products. Phytotoxicity study demonstrated non-toxicity of the biodegraded products for crop plants with respect to Triticum aestivum and Sorghum bicolor. Bacillus sp. VUS with its enzyme system could be a useful tool for textile effluent treatment. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Decolorization; GC-MS; Lignin peroxidase; Orange T4LL; Phytotoxicity; Reductases

Assimilatory potential of helicoverpa armigera reared on host (chickpea) and nonhost (cassia tora) diets - Dawkar, Vishal V.; Chikate, Yojana R.; Gupta, Vidya S.; Slade, Susan E.; Giri, Ashok P. (Journal of Proteome Research, 2011)
Adaptation to plant allelochemicals is a crucial aspect of herbivore chemical ecology. To understand an insect ecology, we studied an effect of nonhost Cassia tora seed-based diet (Ct) on growth, development, and molecular responses in Helicoverpa armigera. We employed a comparative approach to investigate the proteomic differences in gut, hemolymph, and frass of H. armigera reared on a normal (chickpea seed-based, Cp) and Ct diet. In this study, a total of 46 proteins were identified by nano-LC-MS(E). Among them, 17 proteins were up-regulated and 29 proteins were down-regulated when larvae were exposed to the Ct diet. Database searches combined with GO analysis revealed that gut proteases engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification were down-regulated in the Ct fed larvae. Proteins identified in H. armigera hemolymph were found to be involved in defense mechanisms. Moreover, proteins found in frass of the Ct fed larvae were observed to participate in energy metabolism. Biochemical and quantitative real-time PCR analysis of selected candidate proteins showed differential gene expression patterns and corroborated with the proteomic data. Our results suggest that the Ct diet could alter expression of proteins related to digestion, absorption of nutrients, adaptation, defense mechanisms, and energy metabolism in H. armigera.
Keywords: adaptation; Cassia tora; Gene expression; Helicoverpa armigera; proteomics

Degradation of tannic acid by cold-adapted klebsiella sp NACASA1 and phytotoxicity assessment of tannic acid and its degradation products - Jadhav, Umesh; Kadu, Sudhir; Thokal, Nilesh; Padul, Manohar; Dawkar, Vishal V.; Chougale, Ashok D.; Salve, Abhay; Patil, Manoj (Environmental Science and Pollution Research, 2011)
The focus of the present study is to know the potential of bacterial isolate for tannic acid degradation at low temperature. Also, we tried to evaluate the suitability of phytotoxicity testing protocol for the determination of tannic acid toxicity. Screening for tannic acid degrading bacterial strains was carried out by using microbial isolation techniques. The 16S rDNA amplicon of the isolate was used to identify the isolate. The effect of different concentrations of tannic acid and its degradation products on germination of Vigna unguiculata was evaluated. The study was carried out to determine total sugar and starch content of the used seeds and even to check the presence of alpha-amylase activity during seed germination. The isolated bacterium was identified as Klebsiella sp NACASA1 and it showed degradation of tannic acid in 40 (+/- 0.85***) h at 15A degrees C and pH 7.0. A gradual decrease in root/shoot length was observed with increasing concentration of tannic acid. There was 95.11 (+/- 0.24**)% inhibition in alpha-amylase activity at 20,000 ppm tannic acid, as compared to control. No such effects were observed on germination, root-shoot length, and alpha-amylase activity with tannic acid degradation products. The results obtained confirmed that tannic acid may act as a toxic agent in plant cells. The simple biodegradation process presented in this study was found to be effective in reducing toxicity of tannic acid. Also, it reveals the potential of soil bacterium to degrade tannic acid at low temperature.
Keywords: Cold-adapted bacterium; Phytotoxicity; Tannic acid degradation

Purification and characterization of bacterial aryl alcohol oxidase from sphingobacterium sp ATM and Its uses in textile dye decolorization - Tamboli, Dhawal P.; Telke, Amar A.; Dawkar, Vishal V.; Jadhav, Shekhar B.; Govindwar, Sanjay P. (Biotechnology and Bioprocess Engineering, 2011)
Aryl alcohol oxidase (AAO) produced by dye decolorizing bacteria Sphingobacterium sp. ATM, was purified 22.63 fold to a specific activity of 21.75 mu mol/min/mg protein using anion exchange and size exclusion chromatography. The molecular weight of the purified AAO was found to be 71 kDa using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and confirmed by zymography of AAO using L-dopa. The enzyme showed substrate specificity towards veratryl alcohol, followed by n-propanol. The optimum pH and temperature of purified AAO were found to be 3.0 and 40 degrees C, respectively. The K(m) and V(max) of AAO was 1.1615 mM and 3.13 mM/min when veratryl alcohol was used as substrate. Sodium azide showed maximum inhibition while ethylenediamine tetra acetic acid (EDTA), L-cysteine and dithiothreitol showed slight inhibition. Metal ions also showed slight inhibition. HPLC analysis confirmed the degradation of Direct Red 5B. The metabolite obtained after decolorization of Direct Red 5B was characterized as 3 diazenyl 7 [-(phenyl carbonyl) amino] naphthalene-2-sulfonic acid using GC-MS analysis.
Keywords: aryl alcohol oxidase; Direct Red 5B; dye decolorization; ion exchange chromatography; Sphingobacterium sp ATM

Molecular insights into resistance mechanisms of lepidopteran insect pests against toxicants - Dawkar, Vishal V.; Chikate, Yojana R.; Lomate, Purushottam R.; Dholakia, Bhushan B.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Proteome Research, 2013)
Insect pests remain a major reason for crop loss worldwide despite extensive use of chemical insecticides. More than B 50% of all insecticides are organophosphates, followed by synthetic pyrethroids, organochlorines, carbamates, and biopesticides, and their continued use may have many environmental, agricultural, medical, and socioeconomic issues. Importantly, only a countable number of insects have acquired the status of crop pests, mostly due to monoculture of crop plants and polyphagous nature of the insects. We focus on A adaptations of Lepidopteran insects to phytochemicals and synthetic pesticides in native and modern agricultural systems. Because of heavy use of chemical insecticides, a strong selection pressure is imposed on insect populations, resulting in the emergence of resistance against candidate compound(s). Current knowledge suggests that insects generally implement a three-tier system to overcome the effect of toxic compounds at physiological, biochemical, and genetic levels. Furthermore, we have discussed whether the adaptation to phytochemicals provides an advantage to the insect while encountering synthetic insecticide molecules. Specific metabolic pathways employed by insects to convert deterrents into less toxic forms or their removal from the system are highlighted. Using the proteomics approach, insect proteins interacting with insecticides can be identified, and their modification in resistant insects can be characterized. Also, systems biology studies can offer useful cues to decipher the molecular networks participating in the metabolism of detrimental compounds.
Keywords: field crops; insect-pests; insecticide; Lepidoptera; proteomics; resistance mechanisms

Agriproteomics of bread wheat: comparative proteomics and network analyses of grain size variation - Dawkar, Vishal V.; Dholakia, Bhushan B.; Gupta, Vidya S. (OMICS-A Journal Of Integrative Biology, 2015)
Agriproteomics signifies the merging of agriculture research and proteomics systems science and is impacting plant research and societal development. Wheat is a frequently consumed foodstuff, has highly variable grain size that in effect contributes to wheat grain yield and the end-product quality. Very limited information is available on molecular basis of grain size due to complex multifactorial nature of this trait. Here, using liquid chromatography-mass spectrometry, we investigated the proteomics profiles from grains of wheat genotypes, Rye selection 111 (RS111) and Chinese spring (CS), which differ in their size. Significant differences in protein expression were found, including 33 proteins uniquely present in RS111 and 32 only in CS, while 54 proteins were expressed from both genotypes. Among differentially expressed proteins, 22 were upregulated, while 21 proteins were downregulated in RS111 compared to CS. Functional classification revealed their role in energy metabolism, seed storage, stress tolerance and transcription. Further, protein interactive network analysis was performed to predict the targets of identified proteins. Significantly different interactions patterns were observed between these genotypes with detection of proteins such as Cyp450, Sus2, and WRKY that could potentially affect seed size. The present study illustrates the potentials of agriproteomics as a veritable new frontier of plant omics research.

Expression of proteins involved in digestion and detoxification are regulated in helicoverpa armigera to cope up with chlorpyrifos insecticide - Dawkar, Vishal V.; Chikate, Yojana R.; More, Tushar H.; Gupta, Vidya S.; Giri, Ashok P. (Insect Science, 2016)
Helicoverpa armigera is a key pest in many vital crops, which is mainly controlled by chemical strategies. To manage this pest is becoming challenging due to its ability and evolution of resistance against insecticides. Further, its subsequent spread on nonhost plant is remarkable in recent times. Hence, decoding resistance mechanism against phytochemicals and synthetic insecticides is a major challenge. The present work describes that the digestion, defense and immunity related enzymes are associated with chlorpyrifos resistance in H. armigera. Proteomic analysis of H. armigera gut tissue upon feeding on chlorpyrifos containing diet (CH) and artificial diet (AD) using nano-liquid chromatography-mass spectrometry identified upregulated 23-proteins in CH fed larvae. Database searches combined with gene ontology analysis revealed that the identified gut proteins engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification. Biochemical and quantitative real-time polymerase chain reaction analysis of candidate proteins indicated that insects were struggling to get nutrients and energy in presence of CH, while at the same time endeavoring to metabolize chlorpyrifos. Moreover, we proposed a potential processing pathway of chlorpyrifos in H. armigera gut by examining the metabolites using gas chromatography-mass spectrometry. H. armigera exhibit a range of intriguing behavioral, morphological adaptations and resistance to insecticides by regulating expression of proteins involved in digestion and detoxification mechanisms to cope up with chlorpyrifos. In these contexts, as gut is a rich repository of biological information; profound analysis of gut tissues can give clues of detoxification and resistance mechanism in insects.
Keywords: chlorpyrifos; Helicoverpa armigera; insecticide resistance; proteomics; real-time PCR

Parasitism by Chelonus blackburni (Hymenoptera) affects food consumption and development of Helicoverpa armigera (Lepidoptera) and cellular architecture of the midgut - Sanap, Yogita; Dawkar, Vishal V.; Giri, Ashok P.; Sen, Avalokiteswar; Pandit, Radhakrishna S. (Journal of Asia-Pacific Entomology, 2016)
Biological control agents are vital components of an integrated pest management strategy, and this is frequently referred to as natural control. Natural enemies of insect pests include predators, parasitoids, and pathogens. Among them, a parasitoid, Chelonus blackburni (Cameron), was found to be the best biological control agent for the polyphagous pest, Helicoverpa armigera (Hubner). C. blackburni alters the feeding performance of H. annigera larvae upon parasitism and as a result severely affects growth and development. Moreover, it shortens the feeding period of H. armigera and increases mortality. Furthermore, total hemocyte count (THC) was significantly decreased in parasitized larvae than control. Parasitized H. armigera had 26% less number of blood cells compared to healthy larvae. Histological studies showed that the structure of midgut of H. annigera is drastically affected by C. blackburni leading to reduced food consumption, which ultimately led to larval death. The present study provides an insight to changes involved in H. annigera due to parasitism by C blackburni, a parasite that could be used as an effective biocontrol agent to manage H. armigera. (C) 2015 Korean Society of Applied Entomology, Taiwan Entomological Society and Malaysian Plant Protection Society. Published by Elsevier B.V. All rights reserved.

RNAi of selected candidate genes interrupts growth and development of Helicoverpa armigera - Chikate, Yojana R.; Dawkar, Vishal V.; Barbole, Ranjit S.; Tilak, Priyadarshini V.; Gupta, Vidya S.; Giri, Ashok P. (Pesticide Biochemistry and Physiology, 2016)
Helicoverpa armigera is one of the major crop pests and is less amenable to current pest control approaches. RNA interference (RNAi) is emerging as a potent arsenal for the insect pest control over current methods. Here, we examined the effect on growth and development in H. armigera by targeting various enzymes/proteins such as proteases like trypsins (HaTry2, 3, 4 and 6), chymotrypsin (HaChy4) and cysteine protease like cathepsin (HaCATHL); glutathione S-transferases (HaGST1a, 6 and 8); esterases (HaAce4, HaJHE); catalase (HaCAT); super-oxide-dismutase (HaCu/ZnSOD); fatty acid binding protein (HaFabp) and chitin deacetylase (HaCda5b) through dsRNA approach. Significant downregulation of cognate mRNA expression and reduced activity of trypsin and GST-like enzyme were evident upon feeding candidate dsRNAs to the larvae. Among these, the highest mortality was observed in HaAce4 dsRNA fed larvae followed by HaJHE; HaCAT; HaCuZnSOD; HaFabp and HaTry3 whereas remaining ones showed relatively lower mortality. Furthermore, the dsRNA fed larvae showed significant reduction in the larval mass and abnormalities at the different stages of H. armigera development compared to their control diets. For example, malformed larvae, pupae and moth at a dose of 60 pg/day were evident in high number of individual insects fed on dsRNA containing diets. Moreover, the growth and development of insects and moths were retarded in dsRNA fed larvae. These findings might provide potential new candidates for designing effective dsRNA as pesticide in crop protection. (C) 2016 Elsevier Inc. All rights reserved.

Improved tolerance against helicoverpa armigera in transgenic tomato over-expressing multi-domain proteinase inhibitor gene from capsicum annuum - Tanpure, Rahul S.; Barbole, Ranjit S.; Dawkar, Vishal V.; Waichal, Yashashree A.; Joshi, Rakesh S.; Giri, Ashok P.; Gupta, Vidya S. (Physiology and Molecular Biology of Plants, 2017)
Plant proteinase inhibitors (PIs) are plant defense proteins and considered as potential candidates for engineering plant resistances against herbivores. Capsicum annuum proteinase inhibitor (CanPI7) is a multi-domain potato type II inhibitor (Pin-II) containing four inhibitory repeat domains (IRD), which target major classes of digestive enzymes in the gut of Helicoverpa armigera larvae. Stable integration and expression of the transgene in T1 transgenic generation, were confirmed by established molecular techniques. Protein extract of transgenic tomato lines showed increased inhibitory activity against H. armigera gut proteinases, supporting those domains of CanPI7 protein to be effective and active. When T1 generation plants were analyzed, they exhibited antibiosis effect against first instar larvae of H. armigera. Further, larvae fed on transgenic tomato leaves showed delayed growth relative to larvae fed on control plants, but did not change mortality rates significantly. Thus, better crop protection can be achieved in transgenic tomato by overexpression of multi-domain proteinase inhibitor CanPI7 gene against H. armigera larvae.

Nutritional quality and antioxidant activity of wheatgrass (Triticum aestivum) unwrap by proteome profiling and DPPH and FRAP assays - Parit, Santosh B.; Dawkar, Vishal V.; Tanpure, Rahul S.; Pai, Sandeep R.; Chougale, Ashok D. (Journal of Food Science, 2018)
Precious contribution of plants in the field of medicine is very well known. Wheat (Triticum aestivum) seeds and seedlings are an important source of food and feed due to the presence of various health-promoting compounds. Proteomic analysis of three seed developmental stages (0, 8, and 16 days after germination [DAG]) of wheat was carried out using liquid chromatography-mass spectrometry. A total of 297 proteins were identified and their functional annotation revealed that a majority of them were involved in preventing many diseases, oxidative stress, primary metabolism, storage, and energy related mechanisms. Particularly to mention, peroxidases, superoxide dismutases, and cytochromes are abundantly present in wheatgrass. In the ferric-reducing antioxidant power assay, antioxidant activity was increased by 1.55 times after 16 DAG as compared to 0 DAG, however it was decreased after 8 DAG. The antioxidant activity of the plant extracts by DPPH had an increasing trend after all the three time points. The percent radical scavenging activity of extract by DPPH was 15, 22, and 30 after 0, 8, and 16 DAG, respectively. Observations obtained revealed that antioxidant power of the plants is directly proportional to the age of seedlings. Data attained on wheatgrass showing that it can be a strong antioxidant agent due to its free radical scavenging activity and could be used in stress and nourishing human health. Practical ApplicationWheatgrass contains minerals, phytochemicals, active enzymes, and vitamins that can be easily absorbed. The consumption of wheatgrass juice can give better health benefits. Information about beneficial properties of wheat grass juice is clearly mentioned in this work.Proteins found in wheatgrass are known to be involved in preventing many diseases, oxidative stress, primary metabolism, storage, and energy-related mechanisms. Results of this work revealed that Triticum aestivum seedlings can act as an antioxidant agent due to their free radical scavenging activity and can be constructive to control or treat many health complications. From all these results we believed that wheatgrass can be used for the nourishment of humans.
Keywords: Antioxidant; LC-MSE; peroxidase; proteomics; Triticum aestivum; wheatgrass

Azadirachtin-A from azadirachta indica impacts multiple biological targets in cotton bollworm helicoverpa armigera - Dawkar, Vishal V.; Barage, Sagar H.; Barbole, Ranjit S.; Fatangare, Amol; Grimalt, Susana; Haldar, Saikat; Heckel, David G.; Gupta, Vidya S.; Thulasiram, Hirekodathakallu V.; Svatos, Ales.; Giri, Ashok P. (ACS Omega, 2019)
Azadirachtin-A (AzaA) from the Indian neem tree (Azadirachta indica) has insecticidal properties; however, its molecular mechanism remains elusive. The ``targeted and nontargeted proteomic profiling'', metabolomics, matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) imaging, gene expression, and in silico analysis provided clues about its action on Helicoverpa armigera. Fourth instar H. armigera larvae fed on AzaA-based diet (AzaD) suffered from significant mortality, growth retardation, reduced larval mass, complications in molting, and prolonged development. Furthermore, death of AzaD-fed larvae was observed with various phenotypes like bursting, blackening, and half-molting. Liquid chromatography-mass spectrometry (LC-MS) data showed limited catabolic processing of ingested AzaA and dramatic alternations of primary metabolism in H. armigera. MALDI-TOF imaging indicated the presence of AzaA in midgut of H. armigera. In the gut, out of 79 proteins identified, 34 were upregulated, which were related to digestion, immunity, energy production, and apoptosis mechanism. On the other hand, 45 proteins were downregulated, including those from carbohydrate metabolism, lipid metabolism, and energy transfer. In the hemolymph, 21 upregulated proteins were reported to be involved in immunity, RNA processing, and mRNA-directed protein synthesis, while 7 downregulated proteins were implicated in energy transfer, hydrolysis, lipid metabolism, defense mechanisms, and amino acid storage-related functions. Subsequently, six target proteins were identified using labeled AzaA that interacted with whole insect proteins. In silico analysis suggests that AzaA could be efficiently accommodated in the hydrophobic pocket of juvenile hormone esterase and showed strong interaction with active site residues, indicating plausible targets of AzaA in H. armigera. Quantitative polymerase chain reaction analysis suggested differential gene expression patterns and partly corroborated the proteomic results. Overall, data suggest that AzaA generally targets more than one protein in H. armigera and hence could be a potent biopesticide.

Genomic determinants of entomopathogenic fungi and their involvement in pathogenesis - Vidhate, Ravindra P.; Dawkar, Vishal V.; Punekar, Sachin A.; Giri, Ashok P. (Microbial Ecology, 2023)
Entomopathogenic fungi offer an effective and eco-friendly alternative to curb insect populations in biocontrol strategy. The evolutionary history of selected entomopathogenic fungi indicates their ancestral relationship with plant endophytes. During this host shifting, entomopathogenic fungi must have acquired multiple mechanisms, including a combination of various biomolecules that make them distinguishable from other fungi. In this review, we focus on understanding various biochemical and molecular mechanisms involved in entomopathogenesis. In particular, we attempt to explain the indispensable role of enlarged gene families of various virulent factors, viz. chitinases, proteases, lipases, specialized metabolites, and cytochrome P450, in entomopathogenesis. Our analysis suggests that entomopathogenic fungi recruit a different set of gene products during the progression of pathogenesis. Knowledge of these bio-molecular interactions between fungi and insect hosts will allow researchers to execute pointed efforts towards the development of improved entomopathogenic fungal strains.
Keywords: Biocontrol; Chitinases; Endophytic fungi; Entomopathogenic fungi; Hydrolytic enzymes; Insect pests